Goat Meat Production and Quality 2011
DOI: 10.1079/9781845938499.0337
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding system and diet on body lipid composition of young goats.

Abstract: The objective of this chapter is to present findings from our experimental work, as well as from other research institutes, related to the composition and quality of goat meat, particularly the lipid profile, with emphasis on dietary factors and feeding programmes. This topic is of current concern as the fatty acid (FA) composition of ruminant meats and fats contains essential FAs for health, conjugated linoleic acids (CLAs), which reduce the risks of cardiovascular diseases and cancers. It also plays a role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…In contrast, the post-weaning ADG (45-60 d period) of N45 kids decreased by only 28.2% with respect to the pre-weaning ADG (30-45 d period). This agrees with Morand-Fehr et al (1982), who argue that whereas earlier it is performed the weaning more pronounced is the weaning shock.…”
Section: Intake and Growth Performancesupporting
confidence: 90%
See 2 more Smart Citations
“…In contrast, the post-weaning ADG (45-60 d period) of N45 kids decreased by only 28.2% with respect to the pre-weaning ADG (30-45 d period). This agrees with Morand-Fehr et al (1982), who argue that whereas earlier it is performed the weaning more pronounced is the weaning shock.…”
Section: Intake and Growth Performancesupporting
confidence: 90%
“…During the first two weeks of study, the A45 kids showed the lowest ADG, even though these animals had the highest total DM intake during the same period. This was clearly due to the lower feed efficiency achieved with the milk replacer and is consistent with Morand-Fehr et al (1982) and Perez et al (2001), who affirm that the lower feed efficiency of milk replacer may be due to a lower nutritional quality and a slower digestive utilization.…”
Section: Intake and Growth Performancesupporting
confidence: 84%
See 1 more Smart Citation
“…The goats were milked manually twice a day, at 7·00 a.m. and 6·00 p.m. Body condition score was evaluated at the beginning of the research period for all goats using the lumbar system by Morand-Fehr et al (1992). The goats were homogenous for BCS (PRIM goats: 1·85 ± 0·16, MID goats 2·16 ± 0·13 and MULTI goats 2·35 ± 0·16) in the beginning of the research with no statistically significant difference between the groups.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 19 mixed-breed goats were selected as oocyte donors, 10 aged between 1.3 ± 0.2 years and weighing 26.5 ± 2.0 kg, and nine non-lactating goats, aged between 7.0 ± 1.0 years and weighing 42.8 ± 2.1 kg. Both groups exhibited homogenous body condition scores (2.8 ± 0.1) on a scale of 1 to 5 adapted from Morand–Fehr and Gall (1981) . The goats were allocated in the Experimental Farm of School Veterinary Medicine, State University of Ceará (UECE), located in Guaiúba, CE, in the equatorial zone (4º2’23”S and 38º38’14”W) and subjected to 30–45 days of adaptation to environmental and food conditions with balanced diet as per their nutritional requirements.…”
Section: Methodsmentioning
confidence: 99%